Development of Interactive E-Module based on Learning Management System (LMS) in English for IT Course - Prakoso, Gita Hilmi; Novitasari, Ani; Zulfikar, Gilang; Utami, Helidatasa (U-Jet Unila Journal of English Language Teaching, 2025)
This study aims to develop an interactive e-module based on Learning Management System (LMS) in English for IT course to improve learning effectiveness. This e-module is designed by integrating interactive elements such as videos, quizzes, interactive exercises, and online discussions, which aim to support the understanding of technical English concepts in the field of information technology. This study uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. At the implementation stage, the e-module was tested on students of the Software Engineering study program at the Lampung State Polytechnic. Data were collected through user satisfaction questionnaires, and observations, and analyzed descriptively to evaluate the quality of the e-module based on aspects of readability, interactivity, and achievement of learning objectives. The results of the study indicate that this LMS-based interactive e-module is effective in improving students' understanding of English for IT materials and is able to facilitate more independent, flexible learning, and in accordance with the needs of the digital era.